Multilocus Sequence Typing Analysis of Carbapenem-Resistant Acinetobacter baumannii in a Chinese Burns Institute - Huang, Guangtao; Yin, Supeng; Gong, Yali; Zhao, Xia; Zou, Lingyun; Jiang, Bei; Dong, Zhiwei; Chen, Yu; Chen, Jing; Jin, Shouguang; Yuan, Zhiqiang; Peng, Yizhi (Frontiers in Microbiology, 2016)
Acinetobacter baumannii is a leading pathogen responsible for nosocomial infections. The emergence of carbapenem-resistant A. baumannii (CRAB) has left few effective antibiotics for clinicians to use. To investigate the temporal evolutionary relationships among CRAB strains, we collected 248 CRAB isolates from a Chinese burns institute over 3 years. The prevalence of the OXA-23 gene was detected by polymerase chain reaction. Multilocus sequence typing was used to type the CRAB strains and eBURST was used to analyze their evolutionary relationships. Wood surfaces (41%), sputa (24%), catheters (15%) and bloods (14%) were the four dominant isolation sources. Except for minocycline (33.5%) and sulbactam/cefoperazone (74.6%), these CRAB strains showed high resistance rates (> 90%) to 16 tested antibiotics. The 248 isolates fall into 26 sequence types (ST), including 9 known STs and 17 unknown STs. The majority (230/248) of these isolates belong to clonal complex 92 (CC92), including eight isolates belonging to seven unreported STs. A new clonal complex containing 11 isolates grouped into four new STs was identified. The OXA-23 gene was detected at high prevalence among the CRAB isolates and the prevalence rate among the various STs differed. The majority of the isolates displayed a close evolutionary relationship, suggesting that serious nosocomial spreading and nosocomial infections of CRAB have occurred in the burn unit. In conclusion, the main clonal complex for CRAB in this Chinese burn unit remain unchanged during the 3-year study period, and a new clonal complex was identified. CC92 is the dominant complex, and more attention should be directed towards monitoring the new clonal complex we have identified herein.